1998
DOI: 10.1145/277633.277647
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of program spectra

Abstract: A variety of expensive software maintenance and testing tasks require a comparison of the behaviors of program versions. Program spectra have recently been proposed as a heuristic for use in pcrforrning such comparisons. To assess t,lrc potential 11sefulness of spectra in this cont,ext, we conducted an experiment that examined the relationship bct,wccn program spectra and program behavior, and empirically compared several types of spectra. This paper reports the results of that experiment,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…AMPLE works on a hypothesis first stated by Reps et al (1997) and later confirmed by Harrold et al (1998): faults correlate with differences in traces between a correct and a faulty run. A trace is a sequence of actions observed over the lifetime of a program.…”
Section: How Ample Workmentioning
confidence: 97%
“…AMPLE works on a hypothesis first stated by Reps et al (1997) and later confirmed by Harrold et al (1998): faults correlate with differences in traces between a correct and a faulty run. A trace is a sequence of actions observed over the lifetime of a program.…”
Section: How Ample Workmentioning
confidence: 97%
“…Harrold et al [13] give an overview of different types of program spectra. There exist several similarity coefficients to numerically express the degree of similarity, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Program (component) activity is recorded in terms of program spectra [8]. This data is collected at run-time, and typically consists of a number of counters or flags for the different components of a program.…”
Section: A Basic Definitionsmentioning
confidence: 99%